2016
DOI: 10.1007/s00455-016-9751-5
|View full text |Cite
|
Sign up to set email alerts
|

Tongue Strength is Associated with Grip Strength and Nutritional Status in Older Adult Inpatients of a Rehabilitation Hospital

Abstract: The aim of this cross-sectional study was to investigate whether tongue strength observed in older adult inpatients of a rehabilitation hospital is associated with muscle function, nutritional status, and dysphagia. A total of 174 older adult inpatients aged 65 years and older in rehabilitation (64 men, 110 women; median age, 84 years; interquartile range, 80-89 years) who were suspected of having reduced tongue strength due to sarcopenia were included in this study. Isometric tongue strength was measured usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 33 publications
1
64
1
Order By: Relevance
“…A weak positive correlation was noted between GS and TP, indicators of muscle strength in generalised and oral sarcopenia, respectively ( r = .29, P = .03). Buehring et al and Sakai et al reported a correlation between TP and GS. Our results and previous reports suggest that TP can be suitably employed as an indicator of muscle strength in oral sarcopenia.…”
Section: Discussionmentioning
confidence: 94%
“…A weak positive correlation was noted between GS and TP, indicators of muscle strength in generalised and oral sarcopenia, respectively ( r = .29, P = .03). Buehring et al and Sakai et al reported a correlation between TP and GS. Our results and previous reports suggest that TP can be suitably employed as an indicator of muscle strength in oral sarcopenia.…”
Section: Discussionmentioning
confidence: 94%
“…An age‐related decrease in tongue pressure was found in healthy older individuals, and an association between tongue pressure and dysphagia has been observed in healthy older individuals, stroke patients, and older individuals without known neurological diseases . Additionally, an association between decreased tongue pressure and grip strength was found in community‐dwelling older individuals, and an association between low tongue pressure and nutritional status was observed in older inpatients in a convalescent rehabilitation ward . Furthermore, relationships between whole‐body sarcopenia, low tongue pressure and low mouth opening strength have been shown …”
Section: Mechanisms and Risk Factors Of Dysphagia Caused By Sarcopeniamentioning
confidence: 92%
“…47 Additionally, an association between decreased tongue pressure and grip strength was found in community-dwelling older individuals, 48 and an association between low tongue pressure and nutritional status was observed in older inpatients in a convalescent rehabilitation ward. 49 Furthermore, relationships between whole-body sarcopenia, low tongue pressure and low mouth opening strength have been shown. 50 Whole-body muscle mass loss and sarcopenia are also related to dysphagia.…”
Section: Mechanisms and Risk Factors Of Dysphagia Caused By Sarcopeniamentioning
confidence: 99%
“…Brain representation training‐based interventions such as MI, AO and VMF have been proposed as novel therapeutic tools to facilitate motor cortex activity, with or without the actual exercise, for patients who are unable to perform the movements . In this regard, this type of intervention could have a favourable effect on patients with temporomandibular disorders and those with dysphagia in whom pain sensitivity, tongue weakness or motor and emotional processing could be disrupted and related to the maintenance and appearance of the pathologic condition . The combination of motor control exercises and MI has also shown statistically significant changes in sensorimotor function variables of the craniocervical region and in the subjective perception of fatigue, when compared with exercises performed in isolation .…”
Section: Introductionmentioning
confidence: 99%